Soil Transmitted Helminthes Infection among Pregnant Women in Peri-Urban Areas of Ibadan, Nigeria: A cross-sectional study (2018)
cross sectional facility-based study was conducted among the 326 pregnant women attending antenatal care clinics in six selected Primary Health Care centers, in the peri-urban areas of Ibadan Oyo State. An interviewer administered questionnaire was used to obtain information on the socio-demographic, maternal, environmental characteristics and hygiene practices. Kato-Katz method was used to identify the presence of STH from stool samples. Data were analysed using chi-square and bivariate logistic analysis. RESULTS: The overall prevalence of STH was 13.8%; 95% CI (10.0 -17.7). Ascaris lumbricoides 13.2%: 95% CI (9.5 -16.9) was the most prevalent followed by hookworm infection 0.6% 95% CI (-0.2 – 0.15) and Trichuris trichuria 0.3% 95% CI (- 0.2 – 0.9). Majority of the infection were of light intensity (44 out of 45). Walking bare footed in the home environment increased the likelihood of being infected with STH [OR 1.93 95% CI (1.01 -3.72) p=0.048] compared with women who wore shoes. CONCLUSION: STH infection is prevalent among pregnant women in the peri-urban region of Ibadan. Therefore public health interventions like active surveillance of STH and the prescription of deworming drugs for pregnant women.